Ventilator associated lung injury in severe COVID-19 pneumonia patients – Case Reports: Ventilator associated lung injury in COVID-19. (2021) - Gupta, Vikash Kumar; Alkandari, Buthaina Mohammad; Mohammed, Wasif; Tobar, Ahmed Mohamed; Abdelmohsen, Mohsen Ahmed
Abstract: Management of severe coronavirus disease 2019 requires advanced respiratory support modalities including invasive mechanical ventilation (IMV), continuous positive airway pressure (C-PAP), and non-invasive ventilation ((NIV). IMV leads to either subtle forms of lung injury (pulmonary edema, lung cysts) or more severe form of lung injury manifested as subcutaneous emphysema, pneumomediastinum, and pneumothorax (herein collectively termed barotrauma). We have described two cases showing the two end of spectrum of ventilator associated lung injury (VALI).